Health risk assessment of organochlorine pesticide residues in edible tissue of seafood - Hussein, Mohamed A.; Hammad, Omnya S.; Tharwat, Ahmed E.; Darwish, Wageh S.; Sayed-Ahmed, Ahmed; Zigo, František; Farkašová, Zuzana; Rehan, Ibrahim F. (Frontiers in Veterinary Science, 2022)
One-hundred and twenty random samples of Clupea harengus (C. harengus), Mugil cephalus (M. cephalus), Sardinella aurita (S. aurita), Oreochromis niloticus (O. niloticus), Neptunus pelagicus (N. pelagicus) and Sepia savigngi (S. savigngi) (n = 20 each) were collected from local markets in Mansoura city, Egypt. Samples were checked to see whether any residues of organochlorine pesticides (OCPs) with the application of risk assessment due to their consumption by Mansoura citizens, Egypt. Summation hexachlorocyclohexane (∑HCH) in examined seafood samples ranged from 0.27±0.13 in N. pelagicus to 61.61±52.03 µg.kg-1 in S. aurita. Also, the γ-HCH isomer was considered the more prominent among isomers. Hexachlorobenzene (HCB) was found in five different species, with mean values of 2.03±1.85, 1.5.7±1.17, 0.94±0.87, 0.35±0.06, and 0.18±0.06 µg.kg-1 in C. harengus, S. aurita, M. cephlaus, O. niloticus, and S. savigngi. Summation of Heptachlors (∑HPTs) was 10.19±7.63, 1.27±0.26, 2.58±0.11, 0.95±0.12, 0.21±0.11 and 0.32±0.03 µg.kg-1 of wet weight in examined C. harengus, M. cephlaus, S. aurita, O. niloticus, N. pelagicus, and S. savigngi. Aldrin and dieldrin residues were 3.75±1.31 and 4.86±1.33 µg.kg-1 in C. harengu meanwhile they were 1.61±0.77 and 0.78±0.04 µg.kg-1in M. cephalus. Dichlorodiphenyldichloroethylene (pp-DDE) was dominant in all examined species within different concentrations 5.08±4.12, 0.98±0.10, 3.07±0.91, 0.93±0.27, 0.08±0.01 and 0.35±0.02 µg.kg-1 in C. harengus, M. cephlaus, S. aurita, O. niloticus, N. pelagicus and S. savigngi, respectively. All examined seafood samples were lower than the recommended maximum residue limit. Also, the estimated daily intake was less than the permitted daily intake. Non-carcinogenic indices of target hazard quotient and hazard index for OCPs in all examined species were less than 1.